Vytápění bytového domu - Votoček, Libor; Libor Votoček (České vysoké učení technické v Praze, 2019)
Tato bakalářská práce se zabývá návrhem vytápění pro zvolený bytový dům a studií na téma porovnání systémů vytápění pro bytové domy. Projekt vytápění obsahuje výpočet tepelných ztrát jednotlivých místností, návrh otopných těles sjednotlivými hydraulickými výpočty včetně přeregulování ventilů na tělesech a dimenzí potrubí. Tyto výpočty byly zpracovány v programu RaucadTechcon. Dále jsou vypočteny základní energetické výpočty. Cílem studie je seznámení čtenáře s jednotlivými systémy vytápění pro bytové domy. Výsledkem jsou orientační ceny paliv, investiční a provozní ceny jednotlivých zdrojů vytápění. V závěru studie se vyskytuje celkové zhodnocení a vhodné použití jednotlivých částí vytápění (zdroje, otopná tělesa, distribuce, materiál rozvodů) podle různých parametrů.

This bachelor thesis deals with the design of heating for the selected apartment building and studies on the topic of comparison of heating systems for residential buildings. The heating project contains calculation of heat losses of individual rooms, design of radiators with individual hydraulic calculations including re-regulation of valves on solids and dimensions of pipes. These calculations were processed in the program Raucad Techcon. In addition, basic energy calculations are calculated. The aim of the study is to familiarize readers with individual heating systems for residential buildings. The result is indicative fuel prices, investment and operating prices of individual heating sources. At the end of the study there is a total appreciation and appropriate use of individual rating parts (sources, radiators, distribution, material of distribution) according to various parameters.
Heating System of the Apartment Building
Keywords: tepelné ztráty; otopná tělesa; dimenze potrubí; regulace; Raucad Techcon; studie systému vytápění; heat loss; radiators; dimension of pipe; regulation; Raucad Techcon; studies on the topic of heating systems